STATISTICAL ANALYSIS AND FORECASTING OF SOCIO-ECONOMIC DEVELOPMENT OF MUNICIPAL DISTRICTS OF THE ASTRAKHAN REGION - Almina B. Eldyaeva (Статистика и экономика)
The results of statistical research on the municipal districts of the Astrakhan region in the level of socio-economic development for theperiod 2013 and 1999s, on which basis werethe major factors inﬂ uencing socio-economic development of municipal districts of Astrakhan region, and also on the basis of the estimates ofthe forecast are determined priority directionsand problem areas of development are givenin this article. The use of the method may enhance the effectiveness of actions of Executive bodies of various levels in the process of regulation ofsocio-economic development of society.